Analysis of Meaning in the Song Lyrics of Dato' Jamal Abdillah (Jurnal Bahasa, 2024)
Language has a very close relationship with society because every society needs to communicate with each other. It is also the most effective communication tool in conveying meaning, especially in song. This is because a songwriter needs language to convey meaning that can be understood by the listeners. Every song lyric illustrates the thoughts of the songwriter. Therefore, this study was conducted to identify and analyse the types of meaning contained in the song lyrics of Dato' Jamal Abdillah. Through this study, the researcher identified whether a song contains all types or only a few types of meaning. This study uses qualitative research method, specifically text analysis. The researcher analysed meaning in song lyrics based on the types of meaning presented by Leech (1974). In the analysis, all seven types of meaning were found in the song lyrics of Dato' Jamal Abdillah. The most found types of meaning in his lyrics are conceptual, affective and thematic meanings. All of these types of meaning are used in the song lyrics for a specific purpose, such as to emphasize a word. Since the words used by the songwriter for Dato' Jamal Abdillah are easily comprehensible, the listener can experience and understand the message that is clearly conveyed by the songwriter.Keywords: Language, meaning, lyric, song, types of meaning, songwriterFull text: PDF